Pengembangan Media Pembelajaran KODIOAKTIF (Komik Audio Interaktif) Menggunakan Model 3CM Untuk Peningkatan Literasi Siswa SD - Theresia Delga Christiana; Endang Indarini (Jurnal Pendidikan dan Konseling (JPDK), 2023)
Literacy activities are basic in the world of education, but Indonesia's current condition shows low interest in literacy, especially reading. PISA Data Analysis 2018 Indonesia is in the bottom 10 of the 79 participating countries. The ability of Indonesian students is below that of students in ASEAN countries. This study aims to increase elementary students' reading literacy interest using KODIOAKTIVF learning media (Komik Audio Interaktif) with the 3CM Center learning model. This research is a developmental study by combining the R&D development developed by Sukmadinata with the ASSURE development model. This research uses a type of quantitative research obtained through test questions given before and after the implementation of a limited trial and a type of qualitative research obtained through a student response questionnaire complete with criticism and suggestions. The results showed that the data processing of the Paired Sample T Test data obtained showed the Sig. (2-tailed) equals 0.000 < 0.05. This stated that the pretest was rejected, and there was a significant difference between learning outcomes in the pretest and posttest. As for the assessment of instructional media by the school principal, the results of teacher evaluations and student responses were sequentially 91.9%, 91.6%, and 94%. The research can be concluded from the results of the tests before and after the trials, and the results of the school's response, especially from students, that the KODIOAKTIV learning media (Komik Audio Interaktif) with the 3CM Center learning model can improve elementary school students' reading literacy. Keywords: Literacy, Learning Media, 3CM Center learning model, Audio Comics.